What was hot at the fourth World Fisheries Congress?* - Ratana Chuenpagdee; Alida Bundy (Fish and Fisheries, 2006)
Given the current crisis in global fisheries, how well are we doing at managing fisheries? This short paper describes as summarises the results of a systematic assessment of the scientific papers presented at the Fourth World Fisheries Congress, the theme of which was ’Reconciling fisheries with conservation’. Over 200 papers were presented, 70% of which were based on natural sciences, focusing on issues such as biodiversity, species at risk, resiliency, ecosystem modelling, and ecosystem indicators. Encouragingly, over 60% of the papers scored medium to high for their potential contribution to reconciling fisheries with conservation. However, although the human dimensions of fisheries were recognized, few studies involved stakeholders beyond their roles of objects to study. Communication of scientific research findings, particularly to the general public, was notably absent and emphasised as one of the key challenges in achieving sustainability and in reconciling fisheries with conservation.